Determinants of RFID Adoption in Supply Chain among Manufacturing Companies in China: A Discriminant Analysis - Wen,Liu (Universidad Alberto Hurtado. Facultad de Economía y Negocios, 2009)
The growth of China's economy hinges to a large extent on the ability of the industry to operate more efficiently and effectively in the global supply chain system. China's manufacturing companies should pay attention to adopt more efficient supply chain technologies to provide better services for their customers. China has initially carried out research and development and industrialization of technology related to RFID and begun to apply in some areas in recent years. This article studies the determinant factors of the RFID adoption by manufacturing companies in China. The population of this study is manufacturing companies in China that are registered under Federation of China Manufacturers. A questionnaire survey is conducted to study the adoption of RFID by China's manufacturing industry. This study reveals that the environment, organization, technology and product have the impact on the adoption of RFID in China. Organization should be given strategic attention to improve employee participation in adopting RFID as a strategic tool..